2016
DOI: 10.1002/jaba.329
|View full text |Cite
|
Sign up to set email alerts
|

Interactive computer training to teach discrete-trial instruction to undergraduates and special educators in Brazil: A replication and extension

Abstract: Discrete-trial instruction (DTI) is a behavioral method of teaching young children with autism spectrum disorders (ASD) that has received a significant amount of research support. Because of a lack of qualified trainers in many areas of the world, researchers have recently begun to investigate alternative methods of training professionals to implement behavioral teaching procedures. One promising training method is interactive computer training, in which slides with recorded narration, video modeling, and embe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
55
1
15

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(74 citation statements)
references
References 13 publications
3
55
1
15
Order By: Relevance
“…This finding suggests the difference in scores between the two groups could be due to the lack of rehearsal with feedback during portions of the CBI program. Future research could examine the use of CBI that includes more active response activities with feedback, to train participants to implement DTT (e.g., Higbee et al, 2016). In addition, the number of attempts during active response activities could be recorded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding suggests the difference in scores between the two groups could be due to the lack of rehearsal with feedback during portions of the CBI program. Future research could examine the use of CBI that includes more active response activities with feedback, to train participants to implement DTT (e.g., Higbee et al, 2016). In addition, the number of attempts during active response activities could be recorded.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, participants trained with BST reported feeling very competent to perform the task, whereas CBI-trained participants reported feeling somewhat competent. These studies and others (Higbee et al, 2016;Pollard et al, 2014;Serna et al, 2016) illustrate the utility of interactive CBI programs (e.g., video clips, instructions, quizzes) to train people to implement various components of DTT.…”
mentioning
confidence: 90%
“…These modules effectively trained three of four participants to implement DTI at mastery, whereas brief performance feedback was necessary for the remaining participant to reach mastery. Higbee et al (2016) replicated and extended Pollard et al (2014) with four Brazilian university students (study 1) and four Brazilian staff working with individuals with disabilities (study 2). While ICT was effective for three of four staff for whom performance maintained at 1 month, the remaining five participants required performance feedback to demonstrate mastery.…”
Section: Computer-based Trainingmentioning
confidence: 93%
“…Training modalities that are time‐ and cost‐efficient for school districts also would be preferable. A growing body of research has examined the efficacy of technology‐based instruction (e.g., videos, interactive computer programs) for teaching classroom and residential staff to implement behavior‐analytic procedures (e.g., Catania, Almeida, Liu‐Constant, & DiGennaro‐Reed, ; Higbee et al, ; Macurik, O'Kane, Malanga, & Reid, ). Some authors have suggested that computer‐based training may be particularly effective when it includes the more interactive elements of behavioral skills training (BST), including written and vocal instructions, modeling (via embedded videos), and practice with feedback (Higbee et al, ), along with strategies to promote generalization (e.g., multiple exemplars; Stokes & Osnes, ).…”
mentioning
confidence: 99%
“…A similar type of program may be useful for training observers to recognize a broad range of stimulus exemplars that occur within the context of complex classroom environments (e.g., those with simultaneously occurring events). However, in most prior research, computer‐based instruction alone was insufficient for some participants to reach performance‐based criteria when implementing other types of behavioral procedures, even when the instruction included evidence‐based strategies such as multiple exemplar training and hands‐on practice (e.g., Higbee et al, ). Thus, research seems warranted on the efficacy of computer‐based instruction to teach classroom staff to detect and classify potentially relevant antecedents and consequences of behavior.…”
mentioning
confidence: 99%